Reliability analysis of DFIG based wind energy conversion system - Bharti O.P.; Saket R.K.; Nagar S.K. (My University, 2025)
This paper depicts the Reliability evaluation of the DFIG based wind energy conversion system for a WT application and brief description of wind turbine system and DFIG components. To analyze the DFIG reliability, the basic concept of reliability and their historical data analysis of WT have been done. The main contribution of this paper is reliability aspect of the DFIG in details. © 2017 ACM.